Transpersonel psikoloji ve din - Uysal, Saliha (My University, 2007)
Tarih boyunca ruh sağlığı dinden ayrılmaz bir parça olarak görülmüştür. İnsanın manevi yönüyle de ilgilenmek durumunda olan psikolojide “dördüncü güç” olarak nitelendirilen Transpersonel Psikoloji; manevi değerlerin yitirilmeye başladığı bir süreçte, Batı bilimi ile doğunun mistik tecrübelerini buluşturmak amacıyla doğmuştur ve insanın ihtiyaç duyduğu aşkınlık boyutu olan bir psikoloji ekolüdür. Bu çalışmada, öncelikle insanı anlamayı amaçlayan psikoloji ve insanın dinî duygu, düşünce ve davranışını mevzu edinen din psikolojisi tanıtılmıştır. Daha sonra Transpersonel Psikoloji ele alınarak, dinle olan ilişkisi, insanı anlamak için kişinin inanç ve dinî duygularının etkisinin analizi bağlamında tasavvufla ilintili bir şekilde akademik bir çalışmanın sınırları çerçevesinde, kısaca ele alınmıştır.

All through the history, psychological health has been seen as an inseparable piece of religion. Transpersonal Psychology was born with the aim of bringing together the Western Science and the Eastern mystic experiences in a period in which the spiritual worths are being lost and Transpersonel Psychology is determined as “fourth force” in Psychology which also has to deal with the spiritual side of human. Transpersonal Psychology is a psychology school which has a transcendent format as the human needs. In this work, at first psychology, which aims to understand human, and the religion psychology which takes human’s religious emotions, ideas and attitudes as its topic are introduced. Then, Transpersonal Psychology is introduced and its relation with religion is examined shortly in borders of an academic study with connection to Islamic mysticism in context of analyzing the human’s religious belief and emotion to understand human.
Keywords: Din; Din Psikolojisi; Mistisizm; Tasavvuf; Transpersonel Psikoloji